Islamisasi dan Pertumbuhan Institusi Islam di Indonesia - Suhaili, Ridwan; Iswantir, Iswantir (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
The purpose of this discussion is the Origin and Characteristics of Madrasas. The type of research that the writer did was field research which is a qualitative description. Data collection techniques that the authors use are through observation, interviews, and documentation. The validity of the data used is triangulation. The analysis technique that the writer uses according to Miles and Huberman. The results show that Islamization is redefining, rearranging data, rethinking argumentation and rationalization, reassessing goals and doing so in a way that allows the discipline to enrich the vision and cause of Islam. Arab, Persian traders came to Indonesia to trade, since the 7th century AD (1st century H), when Islam first developed in the Middle East. Malacca long before being conquered by the Portuguese (1551 AD), was a major center of trade and shipping traffic. Through Malacca, forest products and spices from all corners of the archipelago were brought to China and India, especially Gujarat, which had direct trade links with Malacca. The first formal, formal madrasah diniyah. The diniyah education curriculum for the formal secondary level must contain content: Citizenship Education, Indonesian Language, Mathematics, Natural Sciences, and Cultural Arts.